A highly active worm-like PtMo nanowire for the selective synthesis of dibenzylamines. Issue 16 (26th February 2018) - Lu, Shuanglong; Xu, Pengyao; Cao, Xueqin; Gu, Hongwei
Abstract : An efficient synthetic pathway of dibenzylamine (DBA) motifs from reductive amination of either aldehydes or nitriles catalyzed by highly active worm-like PtMo nanowires. Abstract : Worm-like nanowires are among the most active nanomaterials. In this study, we report the synthesis of dibenzylamine (DBA) motifs from reductive amination of either aldehydes or nitriles catalyzed by entirely new worm-like PtMo nanowires (PtMo WNWs). Under the assistance of H2 gas, PtMo WNWs can be prepared in a facile manner, following which, their structure and composition are characterized by TEM, XRD, XPS, etc. Upon careful optimization of reaction parameters, the as-prepared PtMo WNWs work effectively in the activation of dihydrogen molecules, and both aldehydes and nitriles can be used as starting materials to fabricate DBAs under mild and green conditions. The reaction kinetics has been investigated, which reveals that the PtMo WNWs show superior activity in the conversion of imines into amines. This study provides a practical advancement in the preparation of amines. Moreover, the protocol reported herein is feasible for the synthesis of worm-like nanostructures with designed composition for various catalytic applications.